El aprendizaje basado en proyectos en la enseñanza de Química en estudiantes de primer año BGU de la Unidad Educativa Dr. Alfredo Pérez Guerrero. - Chiliquinga Villacis, Juan Andrés (2026)
This thesis focuses on the implementation of Project-Based Learning (PBL) in the teaching of chemistry to first-year BGU students at the Dr. Alfredo Pérez Guerrero Educational Unit. Teaching chemistry at this level presents challenges to achieving meaningful learning, as traditional methodologies often hinder the connection between theory and practice and limit the development of critical thinking. In this context, PBL is presented as a strategy capable of enhancing student motivation and academic performance. The objective of the study was to evaluate the effectiveness of PBL in teaching chemistry to this group of students. A mixed-methods approach and a quasi-experimental design were applied, involving 21 students from parallel “A” and the chemistry teacher. Data was collected through interviews, questionnaires, and knowledge tests, which enabled an analysis of current teaching methodologies, student motivation, and academic performance before and after the intervention. The results showed a notable improvement in academic performance, with the average score increasing from 4.76 to 9.14, representing a 92% increase. A paired sampleStudent’s t-test confirmed that the difference was statistically significant (p < 0.001). In conclusion, the implementation of PBL is an effective strategy for strengthening conceptual understanding, motivation, and students’ active participation in chemistry.